PERANCANGAN BUKU KATALOG INTERAKTIF HIJAB BERKALA-KALA YOGYAKARTA DENGAN TEKNOLOGI AR - Tri Widadijo, Wahju; Aflaha, Muhamad (AKSA: Jurnal Desain Komunikasi Visual, 2025)
Berkala-Kala is a hijab brand that has been operating online since its inception in 2020, targeting Muslim women aged 18 to 35 from the Gen Z and Millennial segments. Despite offering a variety of high-quality pashmina products, the brand faced challenges such as declining customer engagement, limited product try on experiences due to its online-only nature, and increasing competition in the hijab industry. To address these issues, this design project proposed an interactive hijab catalog that combines augmented reality (AR) technology and physical fabric samples. This project was developed using the design thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. Data was collected through interviews and observations, followed by user testing with five respondents using the System Usability Scale (SUS) method. The final prototype integrated two main interactive features: real fabric samples attached to each page of the catalog and an AR-based virtual try-on experience accessible via QR code. These features were designed to simulate the tactile and visual experience of shopping in-store. The SUS evaluation resulted in a score of 88.5, which is categorized as "very good", indicating a high level of usability and user satisfaction. Overall, the interactive catalog effectively enhances the user experience, provides innovative product engagement, and supports Berkala-Kala in maintaining competitiveness in the ever-growing hijab market.